2011
DOI: 10.1002/art.30288
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis susceptibility genes influence the association between hip morphology and osteoarthritis

Abstract: Objective. The identified osteoarthritis (OA) susceptibility genes are mainly active in skeletal development and could thus affect joint geometry. Because nonoptimal joint geometry is a risk factor for the development of OA, we investigated if and how the path that leads from nonoptimal joint geometry to OA of the hip is influenced by these genes.Methods. The shape of the hips of subjects in the Genetics, Osteoarthritis and Progression Study, consisting of sibling pairs with symptomatic OA at multiple joint lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 13 publications
(13 reference statements)
1
55
1
Order By: Relevance
“…However, this approach has been successfully applied to better understand disease biology in related complex traits, including joint shape and pain. [46][47][48][49][50] The results of our analyses show that, if further replication is targeted to the specific OA endophenotypes, study power may improve from nearly 0% in the traditional approach to 80% in a sample size of <5000 cases. We used post hoc power calculations, applying the observed variances from the study population of interest to exemplify the difference in the statistical power of the tests we performed.…”
Section: Discussionmentioning
confidence: 79%
“…However, this approach has been successfully applied to better understand disease biology in related complex traits, including joint shape and pain. [46][47][48][49][50] The results of our analyses show that, if further replication is targeted to the specific OA endophenotypes, study power may improve from nearly 0% in the traditional approach to 80% in a sample size of <5000 cases. We used post hoc power calculations, applying the observed variances from the study population of interest to exemplify the difference in the statistical power of the tests we performed.…”
Section: Discussionmentioning
confidence: 79%
“…Finally, our replication cohorts mainly comprised independent populations of children recruited prospectively with a firm diagnosis of DDH, and in whom the EAF and odds ratio of association for the primary variant signal was almost identical as that found in the NJR discovery sample. DDH is a risk factor for degenerative disease at the hip 11,12,23 , and osteoarthritis susceptibility genes influence the association between hip morphology and osteoarthritis 15,24,25 . We therefore also examined whether we were simply detecting osteoarthritis-associated genetic loci in our DDH discovery cohort, as case identification required NJR registration for a hip replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Bos et al (54) demonstrated that D2 was upregulated in osteoarthritis-affected joints and that an allelic imbalance (difference in expression of alleles) in patients might explain the positive association between the D2-92Ala variant and osteoarthritis. Waarsing et al (55) postulated that deiodinase variants might increase vulnerability of cartilage in patients with a predispository non-optimal bone shape and showed a higher risk for osteoarthritis in carriers of the D2-ORF a -Gly3Asp polymorphism. The exact role of deiodinase polymorphism in the genesis or progression of osteoarthritis has yet to be disentangled.…”
Section: Risk For Osteoarthritismentioning
confidence: 99%